Measuring the actual voltage of a triboelectric nanogenerator using the non-grounded method. (November 2020) - Zhang, Wenhe; Gu, Guangqin; Qin, Huaifang; Li, Sumin; Shang, Wanyu; Wang, Tingyu; Zhang, Bao; Cui, Peng; Guo, Junmeng; Yang, Feng; Cheng, Gang; Du, Zuliang
Abstract: Measuring the voltage, including open-circuit voltage ( V oc ) and output voltage, is of great importance for evaluating the performances of a triboelectric nanogenerator (TENG). However, since one electrode of TENG is connected to the ground in the traditional measurement methods, the charges in this electrode are transferred to the ground, causing the underestimated voltage values. To solve this problem and measure the actual voltage, the non-grounded measurement configuration has been proposed here, in which both electrodes of the TENG are disconnected with the ground. From the measurement results of V oc and output voltage by three non-grounded methods, it is obtained that the voltage ratio of non-grounded methods to traditional grounded methods are about 2.0 and 1.5 for sliding type and vertical type TENGs, respectively. The finite element simulation results for TENGs with three different modes match well with the measurement results. Furthermore, it is simulated that the voltage ratio of non-grounded to grounded methods is dependent on the parameters of the TENGs, such as the size of electrodes and the separation distance between them. Also, the non-grounded method has been applied in the TENG-induced micro-plasma to demonstrate its ability to measure the actual output voltage. The non-grounded measurement methods proposed here can measure the actual voltage of TENGs, which are of great significance to accurately evaluating the performances of TENGs. Graphical abstract: This paper proposed the non-grounded measurement configuration to measure the actual voltage of a TENG, in which both electrodes of the TENG are disconnected with the ground. It is found that the voltage ratio of non-grounded methods to traditional grounded methods are about 2.0 and 1.5 for sliding type and vertical type TENGs, respectively. Image 1 Highlights: Charges in the electrode connecting to the ground are transferred to the ground, causing underestimated voltages. To measure the actual voltage, the non-grounded measurement configuration has been proposed. The voltage ratio of non-grounded to grounded methods are 2.0 and 1.5 for sliding and vertical type TENGs, respectively. The non-grounded measurement methods are of great significance to evaluating the performances of TENGs.